The Comparison of The Use of Antiviral Drugs Favipiravir and Remdesivir on The Outcome of Covid-19 Patients at RSM Ahmad Dahlan - Fendy Prasetyawan; Lisa Savitri; Yuneka Saristiana; Shinta Mayasari; Novyananda Salmasfattah (CV. ULIL ALBAB CORP, 2025)
This study aims to compare the usage patterns, effectiveness, and therapy outcomes of two antiviral drugs, Favipiravir and Remdesivir, in the treatment of COVID-19 at Muhammadiyah Ahmad Dahlan Hospital, Kediri City. A total of 71 medical records of patients treated with Favipiravir and 50 treated with Remdesivir were analyzed, focusing on patient demographics, drug usage, and therapy outcomes. The patient characteristics reveal that Favipiravir was more commonly used in older patients (aged >65 years), while Remdesivir was more frequent in younger patients (aged 0-5 years). In terms of drug usage, Favipiravir was prescribed to 58.7% of patients, compared to 41.3% for Remdesivir. Both antivirals demonstrated high recovery rates, with Favipiravir achieving a 100% recovery rate and Remdesivir 98%. Evaluation of drug effectiveness showed that Favipiravir was superior in reducing CRP levels (34.78) compared to Remdesivir (7.74), while Remdesivir had a shorter average length of stay (5.68 days) than Favipiravir (8.67 days). These findings suggest that while Favipiravir is more effective in reducing inflammation, Remdesivir is more efficient in accelerating patient recovery. Both drugs play significant roles in COVID-19 management, with their use tailored to patient needs.